Microporous Electrode Binders for Anion Exchange Membrane Water Electrolyzers - Khalid, Hamza; Plevova, Michaela; Bui, Trung Tuyen; Najibah, Malikah; Hnat, Jaromir; Bouzek, Karel; Henkensmeier, Dirk (Wiley - V C H Verlag GmbbH & Co., 2024)
In anion exchange membrane (AEM) water electrolyzers, AEMs separate hydrogen and oxygen, but should efficiently transport hydroxide ions. In the electrodes, catalyst nanoparticles are mechanically bonded to the porous transport layer or membrane by a polymeric binder. Since these binders form a thin layer on the catalyst particles, they should not only transport hydroxide ions and water to the catalyst particles, but should also transport the nascating gases away. In the worst case, if formation of gases is >> than gas transport, a gas pocket between catalyst surface and the binder may form and hinder access to reactants (hydroxide ions, water). In this work, the ion conductive binder SEBS-DABCO is blended with PIM-1, a highly permeable polymer of intrinsic microporosity. With increasing amount of PIM-1 in the blends, the permeability for water (selected to represent small molecules) increases. Simultaneously, swelling and conductivity decrease, due to the increased hydrophobicity. Ex situ data and electrochemical data indicate that blends with 50% PIM-1 have better properties than blends with 25% or 75% PIM-1, and tests in the electrolyzer confirm an improved performance when the SEBS-DABCO binder contains 50% PIM-1.